The Development of Sex Reassignment Surgery in Thailand: A Social Perspective - Prayuth Chokrungvaranont; Gennaro Selvaggi; Sirachai Jindarak; Apichai Angspatt; Pornthep Pungrasmi; Poonpismai Suwajo; Preecha Tiewtranon (The Scientific World Journal)
This paper reviews the development of gender reassignment in Thailand during the period of 1975–2012, in terms of social attitude, epidemiology, surgical patients’ profile, law and regulation, religion, and patients’ path from psychiatric assessment to surgery. Thailand healthcare for transsexual patients is described. Figures related to the number of sex reassignment surgeries performed in Thailand over the past 30 years are reported. Transsexual individuals are only apparently integrated within the Thail society: the law system of Thailand in fact, does not guarantee to transsexuals the same rights as in other Western countries; the governmental healthcare does not offer free treatments for transsexual patients. In favor of the transsexual healthcare, instead, the Medical Council of Thailand recently published a policy entitled “Criteria for the treatment of sex change, Census 2009.” The goal of this policy was to improve the care of transsexual patients in Thailand, by implementing the Standards of Care of the World Professional Association of Transgender Health. Currently, in Thailand, there are 6 major private groups performing sex reassignment surgery, and mostly performing surgery to patients coming from abroad. Particularly, the largest of these (Preecha’s group) has performed nearly 3000 vaginoplasties for male-to-female transsexuals in the last 30 years.